Effects of planned training and music listened to before a cesarean section on surgical fear, anxiety and depression: A randomized controlled trial - Guney, Demet; Pinar, Sukran Ertekin (Springer Science and Business Media LLC, 2024)
Abstract Purpose This research was conducted to determine the impact of a planned training program and music on fear, anxiety, and depression among women undergoing cesarean section. Methods The sample of the randomized-controlled experimental study consisted of a total of 120 pregnant women (music 40, training 40, and the control 40) scheduled for cesarean section at the Obstetrics Service. Instrumental music from the Turkish music modes (the Hejaz, Neva, and Acemaşıran modes) was played for the music group, a planned training was given for the training group (what a cesarean section is, why a cesarean section should be performed, breastfeeding, mobilization, etc.) before the cesarean section, and no additional interventions were made for the control group. The data were collected using the Personal Information Form, Surgical Fear Questionnaire, and the Hospital Anxiety and Depression Scale. Results After the planned training and listening to music applications, statistically significant differences were found between the music, training, and the control groups in terms of the short-term, long-term sub-scale scores and the overall score of the Surgical Fear Questionnaire and the anxiety sub-scale scores of the Hospital Anxiety and Depression Scale (p < 0.05). Conclusions Listening to music before the cesarean section was effective in reducing women’s short-term and general surgical fears, and the training was also effective in reducing their short-term, long-term, and general surgical fears and anxiety levels. However, the applications did not change depression levels. According to these findings, listening to music and provision of training are recommended to reduce surgical fears and anxiety levels of women before a planned cesarean section.
Keywords: 3. Good health